Analisis Sikap Konsumen: Evaluasi dan Kepercayaan Atribut (Multiattributes Fishbein Approach) - Seprianti Eka Putri (Unib Press Universitas Bengkulu, 2019)
The objective of this research was to know attitude consumer about attribute evaluation and belief at Hand & Body Lotion Mustika Ratu. The object of this research is consumer who used Hand and Body Lotion Mustika Ratu. The analysis methods used Fishbein Multi attributes approach with “Attitude Model” (Ao) and respondent from this study were obtained using purposive sampling techniques. The results showed that evaluation and trust to in attributes have an effect toward consumer attitude. Furthermore, consumer attitudes have shown a positive attitude and like the product.Keywords: attitude, attributes, belief, evaluation, fishbein